Implementasi Cyber Public Relations dalam Meningkatkan Promosi Wisata Setu Babakan Sebagai Destinasi Wisata Budaya Betawi - Afni, Nur Afni Sakinah (Brand Communication, 2024)
This research aims to investigate the role of Cyber Public Relations in enhancing the promotion of Setu Babakan cultural tourism as a distinctive Betawi destination. Employing online surveys, social media analysis, and interviews, the study delves into the impact of digital communication strategies on the awareness and perceptions of visitors towards Setu Babakan. The literature review provides a theoretical foundation on the concept of Cyber Public Relations and the close relationship between cultural tourism and Betawi identity. Research findings depict visitor responses, the effectiveness of social media campaigns, and stakeholder perspectives. The analysis of results indicates the positive contribution of Cyber Public Relations in strengthening the image of Setu Babakan as a cultural tourism destination, while also identifying challenges and opportunities for improvement to enhance the effectiveness of these strategies. The conclusion summarizes the findings and practical implications, while recommendations are presented to support the future development of Cyber Public Relations campaigns in the context of promoting local cultural tourism. This research is expected to contribute to practical and theoretical understanding of the role of digital communication strategies in supporting the growth of cultural tourism in Indonesia.